Penile fracture: experience in 56 cases - Koifman,Leandro (2003)
OBJECTIVE: The aim of this work is to report the diagnostic and therapeutic options for 55 patients with clinical diagnosis of penile fracture. MATERIALS AND METHODS: The patients were retrospectively assessed between 1982 and 2002. The primary diagnostic evaluation method for 55 patients (56 fractures) was clinical history and physical exam. Ten (17.8%) cases required complementary exams. Ultrasound (US) was performed in 2 cases, and magnetic resonance imaging (MRI) in 1 case. Retrograde urethrocystogram was performed in suspicious urethral injury, which happened for 7 patients. RESULTS: Of 56 assessed cases, 49 (89.5%) were submitted to surgical exploration, and only 7 were conservatively conducted. Surgical treatment was performed in 48 patients (49 fractures), in these cases, 47 (95.9%) presented tunica albuginea disruption and solely 2 (4.1%) evidenced lesion of dorsal vein. Ultrasonography confirmed disruption of tunica albuginea in 1 (50%) case, and in the other it was not possible to determinate the origin of the lesion, and the patient was submitted to surgical exploration, which confirmed the condition. MRI was used only in 1 case, confirming the lesion. Among 7 patients submitted to conservative management, until now, 3 (42.8%) required surgical intervention to correct penile chordee. CONCLUSIONS: Penile fracture is an entity of eminently clinical diagnosis, which management should be surgical and immediate, avoiding thus complications related to erectile dysfunction. When suspecting an associated urethral injury, Urethrocystogram is recommended. In cases where there is diagnostic uncertainty, ultrasound and/or MRI may be used to reveal the condition.